Association of Meniscal Injury in Anterior Cruciate Ligament Deficit Knee and Outcome After Surgery - Asaduzzaman, Muhammad; Khanam, Masuma; Harun, Muhammad Eusuf; Islam, Md Towhidul (Mugda Medical College Journal, 2022)
Background: In young active adult population, the anterior cruciate ligament rupture and meniscus tear are common injuries which reduce the activity level and lead to economic burden. Objective: To evaluate the association of meniscal injury in anterior cruciate ligament deficit knee by diagnostic arthroscopy and assess the clinical outcome after surgery (arthroscopic anterior cruciate ligament reconstruction by ipsilateral quadruple Semitendinosus and Gracilis tendon auto graft and partial menisectomy). Methods: This prospective type of longitudinal study was carried out at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh, from January 2014 to December 2015. Purposive sampling was done to include the patients presented with unilateral knee complaints clinically diagnosed as anterior cruciate ligament deficit with or without meniscus injury. The total number of subjects included was 20. Data collection was carried out with pretested questionnaire. After preoperative evaluation and surgery, accelerated rehabilitation protocol was followed. Follow up had been continued up to six months. In Lysholm Knee scoring scale preoperative and postoperative scores were calculated and comparison of mean value was done. Results: The mean age of respondents was 28.2±9.87 years. Among the respondents, male was found 95%. Regarding the occupation, 60% were sportsmen and 25% were students. The causes of injury were sports (75%), accidental fall (15%) and road traffic accident (10%). Medial and lateral meniscus injury was found in 40% and 45% respondents respectively. The rest were found with anterior cruciate ligament injury alone. The mean postoperative hospital stay was 7.18±4.36 days. According to Lysholm Knee Score, the outcome of surgery was excellent in 60%, good in 35% and fair in 5% respondents. The mean preoperative and postoperative Lysholm Knee Score was 54.64±4.365 and 91±8.768 respectively which reflects significant postoperative improvement (p<0.05). Conclusion: Anterior cruciate ligament injury associated with meniscus injury frequently occurs in young population. Reconstruction of the anterior cruciate ligament and partial menisectomy will help people return to their original activity. Mugda Med Coll J. 2022; 5(1): 24-28